Areas of Improvement of Finance Policy in the Process of Advancing of Upgrading the Territorial Economic Activity and Financial Capacity - George Abuselidze (International Business Research, 2013)
On the current stage, an important direction towards completion fiscal regulation is to regionalise economic and social processes, decentralize an important part of state functions on the local authorities. Herewith, to finance the expenditure by attaching appropriate income sources which will strengthen the role of local finances and assist the prosperity of regional economy. At the contemporary stage local budgets country, its separate regions development one of the most powerful leverage. Without them it is impossible political stability as in whole country, as in its separate regions. Local budget funds, social infrastructure forming are one of the major sources. Developed countries local budgets, density spare of social expenditures are higher than the state budgets. Local budget expenditures, especially on social provision spent funds promote in society social conflict softening that in contemporary conditions of each county's sustainable development stipulating factor.
Keywords: 330; fiscal policy; territorial budgets